Effect of Internal Marketing on Employees' Perception of Their Performance - Doshi, Parinda V. (Prabandhan: Indian Journal of Management, 2018)
The services sector in India has remained the most vibrant sector in terms of contribution to national and state incomes. India is ranked at the 11th position in the world with the GDP of about $1185.79 billion as a contribution from its service sectors (Statistics Times, 2017). The banking sector contributes a greater share in the services sector of India. Internal marketing practices are generally followed by the service organizations to maximize their customer satisfaction and hence increaseÂ the performance of the organization. The present study was undertaken to examine the relationship of communication, supervision, intangible benefits, compensation, and intermediary facilities (variables of internal marketing) with the employees' perception on their performance in the banking sector. The relationship between the perception on performance and categorical variables like gender, education, department, and experience was also examined in the given study. Data were collected from the front and back office staff of a private sector bank. Analysis was done using correlation and chi-square test to understand the relationship of categorical and internal marketing variables with performance of the employees at the bank. The results of the study indicated no association among the categorical variables and the variables of internal marketing. It was also observed that only some items of the variable of supervision and intangible benefits had a relationship with the employees' perception of their performance, while rest of the items and variables were found to be independent.